Molecular Identification of Microbial Community in Surface and Undersurface Douchi During Postfermentation. Issue 4 (12th March 2014) - Chen, Tingtao; Wang, Mengjuan; Li, Shengjie; Wu, Qinglong; Wei, Hua
Abstract To find the reason for fermentation failure of surface Douchi during postfermentation, the microbial communities in undersurface and surface samples were investigated using cell counting method and denaturing gradient gel electrophoresis (DGGE). The results showed that the microbial biomass in surface Douchi was obviously different from that in undersurface Douchi even sampled from the same fermentation tanks, and a 10‐ to 100‐fold reduction of microbial cell counts in undersurface had been observed. The bacterial DGGE profile and principal component analysis (PCA) results indicated that only Lactococcus lacts subsp. lactis and Bacillus thermoamylovorans were detected from surface Douchi, while Lactococcus lacts subsp. lactis, Staphylococcus lentus and 2 uncultured strains occupied the dominant positions in undersurface Douchi; when amplified using Bacillus‐specific primers, Bacillus thermoamylovorans, Bacillus subtilis, and Enterobacter sp. were found in undersurface Douchi, while only Bacillus thermoamylovorans were detected from surface Douchi; compared to the bacteria and Bacillus, the DGGE profiles and PCA plot of fungi indicated that the fungal community between surface and undersurface Douchi was similar and mainly composed by yeasts. In this study, we detected the microbial biomass and species in postfermentation stage of Douchi, and the various microbial diversity in undersurface and surface samples might be the cause of the fermentation failure in surface fermentation tanks.